Art therapy for people with psychosis: a narrative review of the literature. (November 2016) - Attard, Angelica; Larkin, Michael
Summary: Art therapy enables individuals to use art to creatively express themselves and communicate differently with themselves, others, and their reality. The National Institute for Health and Clinical Excellence guidelines for psychosis and schizophrenia suggest that arts therapies, which include art therapy, are considered to improve negative symptoms of psychosis. We examined the effectiveness of art therapy for people with psychosis and explored whether art therapy is a meaningful and acceptable intervention in this Review. Seven electronic databases were searched for empirical papers that concerned the use of art therapy for adults with psychosis that were published from 2007 onwards. The search identified 18 papers. High-quality quantitative articles provided inconclusive evidence for the effectiveness of art therapy in adults with psychosis. However, high-quality qualitative articles indicated that therapists and clients considered art therapy to be a beneficial, meaningful, and acceptable intervention, although this conclusion was based on a small number of studies. In this Review, we discuss the theoretical, clinical, and methodological issues in light of the development of more robust research, which is needed to corroborate individuals' experiences and guide evidence-based practice.